GEN Z'S INTENTION TO SHARIA BANKING : THE ROLE OF FINANCIAL LITERACY, RELIGIOSITY, AND DEMOGRAPHICS - Istianah, Nur; Rahayu, Yayuk Sri; Hasibuan, Lempang (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The Islamic banking sector in Malang City shows strong growth potential due to its large youth population. However, Generation Z’s adoption remains low, influenced by financial literacy, religiosity, and demographic factors. This study examines how these variables affect Generation Z’s interest in Islamic banking, using a survey of 204 respondents and multiple linear regression analysis in SPSS 26. Results reveal that financial literacy, religiosity, and demographics positively influence interest, offering insights for banks to develop youth-focused marketing strategies.